Geochronology and geochemistry of late Paleozoic volcanic rocks in eastern Inner Mongolia and their geological significance - Tianyi Liang; Mengmeng Li; Li Wang; Guanhong Wang; Xinglong Tang; Zhuang Li (Open Geosciences)
The Daxing’anling region in Inner Mongolia has always been the most active area of tectonic magmatic activity in the Xingmeng orogenic belt. This study investigated the rock geochemistry of trachyandesite and rhyolite tuff of the Late Carboniferous Gegen Aobao Formation in eastern Inner Mongolia. This study presents new petrography, zircon U-Pb age, and whole-rock geochemical data for the Late Carboniferous Gegenaobao Formation in volcanic rocks in order to constrain their petrogenesis and geodynamic setting. The results indicate that the aluminum content of trachyandesite is relatively high, and the calcium and magnesium content is higher than that of rhyolite tuff, showing a sodium-rich characteristic. It is a quasi-aluminum peraluminous rock, and the europium anomaly is not obvious. The formation age is 304.4 ± 2.3 Ma. The calcium and magnesium content of the rhyolite tuff is relatively low, exhibiting characteristics of calcium alkali and weak peraluminous rocks. It has more obvious characteristics of light and heavy rare earth fractionation and negative europium anomalies, with a formation age of 307.6 ± 2.0 Ma. Comprehensive analysis shows that the magma of Late Carboniferous volcanic rocks in eastern Inner Mongolia mainly originates from the crust, with a deeper source of andesite and partial melting of the mantle material. Both are tectonic environments of continental margin arc volcanic rocks. The Xing’an Block and the Songnen Block completed collision assembly in the Early Carboniferous and were in a post-orogenic extension environment in the Late Carboniferous. The ancient Asian Ocean in the northern part of the Erlian Hegenshan Zhalantun Heihe tectonic belt had already closed in the Late Carboniferous, and the Xingmeng orogenic belt began to enter the orogenic extension stage.